Novel Coronavirus 2019: A Recent Update - Mohammad Mukim; Mahawar, Pawan Kumar; Sharma, Pratishtha; Sharma, Abhay; Roy, Supriya (Talenta Publisher, 2020)
Since last year of December 2019, a virus has been identifying in china’s city of Wuhan, virus name Severe Acute Respiratory Syndrome coronavirus (SARS-CoV-2). 2019 Novel Coronavirus (COVID-19) Disease is a very scary Disease. This disease is a challenge for Human for cure. These virus are effected all over the world’s country like America, Brazil, Turkey, China, Italy, Iran, India, Canada Russia etc., this virus first time reported in relation to the Huainan Seafood Wholesale Market (South China Seafood City Food Market) in Wuhan, China. This market gained media attention after being identified as a point of origin of the 2019–20 coronavirus pandemic. This virus have the common sign & symptoms like pneumonia and show symptoms of fever, headache, joint pain, Common cold, chills, shortness of breath, cough severe pneumonia, dyspnea, renal insufficiency. The detection of 2019- SCoV-like viruses in tiny size, live wild mammals in a market indicates a route of inters species spreading, although the natural loch is not known. This theory assembles a study of the molecular biology fundamental of these infectious agents, with particular prominence on the nature and identify of viral receptors, viral RNA synthesis, and the molecular interactions governing viral assembly.